2022
DOI: 10.24831/jai.v50i2.40674
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Response Selection on Mung Bean Transgressive Segregants

Abstract: Mung bean is one of the essential food crops in Indonesia. Improvement of mung bean varieties is needed to obtain superior mung bean varieties. This study aimed to estimate the selection response and confirm the transgressive segregants in the F4 generation of mung bean crosses. The experiment was carried out from February to May 2021 in the Leuwikopo Experimental Field of IPB University, Bogor, West Java (275 m asl). The experimental design was an augmented-randomized complete block design (RCBD) consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Mardi et al (2022) also reported that transgressive segregants were the genotypes with a higher mean value than check genotypes, and the level of diversity was lower or equal to pure lines. Several studies have also carried out transgressive segregation estimations, including on wheat (Al-Bakry, 2021), mung bean (Jambormias et al, 2015;Maulida et al, 2022), sorghum (Munarti et al, 2022), and chili (Karim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mardi et al (2022) also reported that transgressive segregants were the genotypes with a higher mean value than check genotypes, and the level of diversity was lower or equal to pure lines. Several studies have also carried out transgressive segregation estimations, including on wheat (Al-Bakry, 2021), mung bean (Jambormias et al, 2015;Maulida et al, 2022), sorghum (Munarti et al, 2022), and chili (Karim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the average value, the variance value also requires consideration. A low variance rate indicates that the genotype is increasingly homogeneous (Maulida et al, 2022).…”
Section: Data Recorded and Analysismentioning
confidence: 99%